2017
DOI: 10.30536/j.ijreses.2015.v12.a2687
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove Above Ground Biomass Estimation Using Combination of Landsat 8 and Alos Palsar Data

Abstract: Mangrove ecosystem is important coastal ecosystem, both ecologically and economically. Mangrove provides rich-carbon stock, most carbon-rich forest among ecosystems of tropical forest. It is very important for the country to have a large mangrove area in the context of global community of climate change policy related to emission trading in the Kyoto Protocol. Estimation of mangrove carbon-stock using remote sensing data plays an important role in emission trading in the future. Estimation models of above grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
2
8
1
1
Order By: Relevance
“…This result was in line with (Hamdan et al, 2013;Li et al, 2007) that generated good correlations between vegetation indices and field biomass. Our result was in contrary to (Wicaksono, Danoedoro, Hartono, Nehren, & Ribbe, 2011) and (Winarso et al, 2017) that NDVI values and other vegetation indices had low correlation with field biomass.…”
Section: Mangrove Biomass Estimatingcontrasting
confidence: 99%
See 1 more Smart Citation
“…This result was in line with (Hamdan et al, 2013;Li et al, 2007) that generated good correlations between vegetation indices and field biomass. Our result was in contrary to (Wicaksono, Danoedoro, Hartono, Nehren, & Ribbe, 2011) and (Winarso et al, 2017) that NDVI values and other vegetation indices had low correlation with field biomass.…”
Section: Mangrove Biomass Estimatingcontrasting
confidence: 99%
“…Several methods, which confirmed that remote sensing is possible to estimate mangrove biomass, have been already developed and published. Remote sensing is a great data source facilitating field surveys by avoiding the destructive method and reducing time and cost for field surveys (Anaya et al, 2009;Muhd-Ekhzarizal, Mohd-Hasmadi, Hamdan, Mohamad-Roslan, & Noor-Shaila, 2018;Winarso et al, 2017).…”
Section: Estimation Mangrove Biomassmentioning
confidence: 99%
“…We also have compared our result with Landsat data, where the actual optical images of the Landsat data with textural and spectral characteristics of the canopy and leaves are the main features used to distinguish among mangrove communities. 35,50 According to Fig. 6 the results of the classification of mangroves and nonmangroves on ALOS PALSAR imagery are almost the same as those produced by Landsat imagery.…”
Section: Estimation Of Aboveground Biomass Of Mangrove Forestsmentioning
confidence: 61%
“…In estimating above-ground biomass using remote sensing, NDVI was used following the earlier studies (Hamdan et al, 2013;Manna et al, 2014;Patil et al, 2013;Winarso et al, 2017). A scatter plot between NDVI estimate and AGB calculated in the field was compared.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate estimation of carbon stocks is necessary before taking any measures towards conservation and restoration (Liu et al, 2014). Over the years, there have been several studies on carbon sequestration of mangrove wetlands in China (Li et al, 2006), Malaysia (Hamdan et al, 2013), India (Manna et al, 2014;Patil et al, 2013;Sahu et al, 2016), Indonesia (Winarso et al, 2017), Australia (Tran, 2014). However, little is known about the importance of mangrove wetlands in hyper-arid regions.…”
Section: Introductionmentioning
confidence: 99%